Australian Newspaper Framing of Renewables: The Case of Snowy Hydro 2.0. Issue 1 (2nd January 2022) - Holmes, David; Garas, Brooke; Richardson, Lucy M.
ABSTRACT: Australian media reporting of climate change and renewable energy, along with public perceptions of the science and solutions of climate change, have shifted in ways that have increased pressure on politicians and policy makers. With the promotion of renewable energy central to ending Australia's heavy reliance on fossil fuels, it is critical to understand how this complex intersection of media and politics is evolving with regard to Australia's renewable energy options. Therefore, this paper examines Australian newspaper reporting of a pivotal moment in Australia's renewable energy discourse: the Australian Government's announcement, in March 2017 to expand the seventy-year-old Snowy Mountains Hydroelectric Scheme (known as Snowy 2.0), which marked a turning point in conservative energy policy. Qualitative content analysis reveals that, while political discourse delimited newspaper narratives, the sentiment of the framing was most strongly associated with the partisan alignment of the publishing organization. Regional influences also had a minor association with the framing of renewable energy. Through close analysis of this decisive moment in Australian media's political representation of renewable energy, this paper offers insights that can be used to inform media strategies for renewable energy policy in Australia, and to track changes in framing over time.